Testing the divergence-with-gene flow model of ecological speciation in two species of andean hummingbirds (2010)
The divergence-with-gene-flow model of ecological speciation proposes speciation can proceed despite genetic interchange in populations distributed along environment al gradients, where variable selective regimes act on traits ultimately associated with reproductive isolation. Despite ample evidence for population divergence with gen e flow, studies showing that species-level differences arose in the face of gene flow and assessing the environmental and genetic factors promoting differentiation are scarce. Coeligena helianthea and C. bonapartei are two parapatrically distributed Andean hummingbird sister species that represent a good opportunity to evaluate this mode of speciation because they exhibit high ( and potentially adaptive) phenotypic divergence with low levels of genetic differentiation.